Requirement for a minimum service level framework for cloud providers and users - Khan, Sohail (2019)
Summary of the Presentation 1. Introduction and Justification of the theme Context Problems, Challenges and the Research Question Aim & Objectives 2. Framework Theoretical (Literature Review) Contextual Empirical (Research Design, Proposed Model) 3. Results Presentation & Analysis 4. Conclusion and Recommendations Work Contributions-Recommendation Limitations of Work Future of Work 5. Publications